Passenger Satisfaction Mapping and Service Improvement Priorities for 2026 Eid Transport at Banjarnegara Bus Terminal - Septiana Widi Astuti (IWTJ : International Water Transport Journal, 2026)
Seasonal Eid transport creates a recurring service-quality challenge for bus terminals because passenger demand, operational pressure, information needs, and safety expectations increase simultaneously within a short period. This study aims to assess passenger satisfaction and determine service-improvement priorities during the 2026 Eid transport period at Banjarnegara Bus Terminal. The research used a descriptive quantitative approach based on a questionnaire survey of 51 passengers, field observation, and operational documentation during the homecoming period (15-18 March 2026) and the return-flow period (23-25 March 2026). The data were analyzed using Importance-Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). The results indicate that the overall service-suitability level reached 81.18%, while the CSI value was 73.6%, reflecting a moderate-to-good satisfaction level that still requires targeted improvement. The lowest suitability was found in the fare dimension (74.83%), followed by vehicle facilities and time reliability. IPA mapping identified public toilet cleanliness, vehicle toilet availability, disability facilities, ticket price, and fare-service suitability as the main priority attributes. These findings show that improving sanitation, inclusive facilities, fare transparency, and real-time operational information should become the immediate managerial agenda for strengthening Eid transport services at Banjarnegara Bus Terminal.